2011
DOI: 10.1097/hco.0b013e32834398ba
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter aortic valve replacement: where will we be in 5 years?

Abstract: Evidence is accumulating in support of TAVI for high-risk nonoperative aortic stenosis. Even before the PARTNER cohort A results, comparing TAVI and conventional aortic valve replacement, become available, the next generation devices and technological improvements are well underway to make the procedure even more reproducible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Transcatheter aortic valve implantation (TAVI) has been developed as a treatment strategy for patients with severe aortic stenosis who are at high risk or not eligible for heart surgery [29]. Several studies have demonstrated that MDCT is an ideal imaging modality prior to TAVI, providing isotropic datasets of the aortic root that can be reformatted in any spatial orientation [30][32].…”
Section: Discussionmentioning
confidence: 99%
“…Transcatheter aortic valve implantation (TAVI) has been developed as a treatment strategy for patients with severe aortic stenosis who are at high risk or not eligible for heart surgery [29]. Several studies have demonstrated that MDCT is an ideal imaging modality prior to TAVI, providing isotropic datasets of the aortic root that can be reformatted in any spatial orientation [30][32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, bulky leaflet calcification poses a risk for occlusion of the coronary ostium. 33 The Sapien valve is not affected by sinotubular junction measurements as its profile is lower. However, there should be a minimum distance of 10-11 mm between the aortic annulus and the coronary ostium (particularly the left).…”
Section: Measurements Of the Aortic Annulusmentioning
confidence: 94%
“…Annular/leaflet calcification is required for the placement of the transcatheter valve; however, calcification‐related annular asymmetry residues also lead to paravalvular insufficiency. In addition, bulky leaflet calcification poses a risk for occlusion of the coronary ostium . The Sapien valve is not affected by sinotubular junction measurements as its profile is lower.…”
Section: Aortic Valve Morphology and Coronary Ostiumsmentioning
confidence: 99%
“…In the past decade, the increased usage of TAVI has led to rapid development and improvement in techniques and device designs. To date, the success of TAVI among intermediate‐risk patients has led to attempts to expand its use in younger patients who are low‐risk candidates for SAVR . However, major questions still remain for TAVI before we can generalize this procedure.…”
Section: Introductionmentioning
confidence: 99%